Room-temperature Pd/Ag direct arylation enabled by a radical pathway - Mayhugh, Amy L.; Luscombe, Christine K. (Beilstein Journal of Organic Chemistry, 2020)
Direct arylation is an appealing method for preparing π-conjugated materials, avoiding the prefunctionalization required for traditional cross-coupling methods. A major effort in organic electronic materials development is improving the environmental and economic impact of production; direct arylation polymerization (DArP) is an effective method to achieve these goals. Room-temperature polymerization would further improve the cost and energy efficiencies required to prepare these materials. Reported herein is new mechanistic work studying the underlying mechanism of room temperature direct arylation between iodobenzene and indole. Results indicate that room-temperature, Pd/Ag-catalyzed direct arylation systems are radical-mediated. This is in contrast to the commonly proposed two-electron mechanisms for direct arylation and appears to extend to other substrates such as benzo[b]thiophene and pentafluorobenzene.
Keywords: direct arylation; indole; palladium radical; visible light

(untitled) - Po, R.; Bianchi, G.; Carbonera, C.; Pellegrino, A. (Macromolecules, 2015)

(untitled) - Huang, Y.; Luscombe, C. K. (Chem. Rec., 2019)

(untitled) - Pouliot, J.-R.; Grenier, F.; Blaskovits, J. T.; Beaupré, S.; Leclerc, M. (Chem. Rev., 2016)

(untitled) - Wencel-Delord, J.; Dröge, T.; Liu, F.; Glorius, F. (Chem. Soc. Rev., 2011)

(untitled) - Gensch, T.; Hopkinson, M. N.; Glorius, F.; Wencel-Delord, J. (Chem. Soc. Rev., 2016)

(untitled) - Gobalasingham, N. S.; Thompson, B. C. (Prog. Polym. Sci., 2018)

(untitled) - Rudenko, A. E.; Thompson, B. C. (J. Polym. Sci., Part A: Polym. Chem., 2015)

Polymers: Chemistry and Physics of Modern Materials - Cowie, J. M. G.; Arrighi, V. (CRC Press, 2007)

(untitled) - Zhou, C.; Liang, Y.; Liu, F.; Sun, C.; Huang, X.; Xie, Z.; Huang, F.; Roncali, J.; Russell, T. P.; Cao, Y. (Adv. Funct. Mater., 2014)

(untitled) - René, O.; Fagnou, K. (Org. Lett., 2010)

(untitled) - Colletto, C.; Panigrahi, A.; Fernández-Casado, J.; Larrosa, I. (J. Am. Chem. Soc., 2018)

(untitled) - Lebrasseur, N.; Larrosa, I. (J. Am. Chem. Soc., 2008)

(untitled) - Colletto, C.; Islam, S.; Juliá-Hernández, F.; Larrosa, I. (J. Am. Chem. Soc., 2016)

(untitled) - Islam, S.; Larrosa, I. (Chem. – Eur. J., 2013)

(untitled) - Okamoto, K.; Housekeeper, J. B.; Michael, F. E.; Luscombe, C. K. (Polym. Chem., 2013)

(untitled) - Gooßen, L. J.; Deng, G.; Levy, L. M. (Science, 2006)

(untitled) - Cornella, J.; Lahlali, H.; Larrosa, I. (Chem. Commun., 2010)

(untitled) - Cornella, J.; Lu, P.; Larrosa, I. (Org. Lett., 2009)

(untitled) - Stateman, L. M.; Nakafuku, K. M.; Nagib, D. A. (Synthesis, 2018)

Radicals in organic synthesis - Renaud, P.; Sibi, M. P. (Wiley-VCH, 2001)

(untitled) - Lapointe, D.; Fagnou, K. (Chem. Lett., 2010)

(untitled) - Lebrasseur, N.; Larrosa, I. (Adv. Heterocycl. Chem., 2012)

(untitled) - Seregin, I. V.; Gevorgyan, V. (Chem. Soc. Rev., 2007)

(untitled) - Lane, B. S.; Brown, M. A.; Sames, D. (J. Am. Chem. Soc., 2005)

(untitled) - Deprez, N. R.; Kalyani, D.; Krause, A.; Sanford, M. S. (J. Am. Chem. Soc., 2006)

(untitled) - Kurokhtina, A. A.; Larina, E. V.; Yarosh, E. V.; Lagoda, N. A.; Schmidt, A. F. (Organometallics, 2018)

(untitled) - Zhou, W.-J.; Cao, G.-M.; Shen, G.; Zhu, X.-Y.; Gui, Y.-Y.; Ye, J.-H.; Sun, L.; Liao, L.-L.; Li, J.; Yu, D.-G. (Angew. Chem., Int. Ed., 2017)

(untitled) - Kurandina, D.; Parasram, M.; Gevorgyan, V. (Angew. Chem., Int. Ed., 2017)

(untitled) - Parasram, M.; Chuentragool, P.; Sarkar, D.; Gevorgyan, V. (J. Am. Chem. Soc., 2016)

(untitled) - Liu, Q.; Dong, X.; Li, J.; Xiao, J.; Dong, Y.; Liu, H. (ACS Catal., 2015)

(untitled) - Punji, B.; Song, W.; Shevchenko, G. A.; Ackermann, L. (Chem. – Eur. J., 2013)

(untitled) - Guo, X.-K.; Zhang, L.-B.; Wei, D.; Niu, J.-L. (Chem. Sci., 2015)